(untitled) (PANGEEA, 2025)
In the operation of centralized water supply systems, approximately 90% of used energy is electricity, out of which a significant share, over 80%, is consumed by water distribution in networks equipped with pumping stations. In the last decades, to adapt systems to the variable requirements of users, the water systems are provided with pumps driven by variable speed controlled motors. In order to reduce the power consumption when water is delivered to consumers according to their demands, it is necessary to improve the pumps operating efficiency. The paper presents a series of aspects regarding the defining of the opportunity for retrofitting and rehabilitation of the pumps within the Chiriţa pumping station.